2004
DOI: 10.1002/hrm.20031
|View full text |Cite
|
Sign up to set email alerts
|

The importance of pay in employee motivation: Discrepancies between what people say and what they do

Abstract: Rynes, Colbert, and Brown (2002) presented the following statement to 959 members of the Society for Human Resource Management (SHRM): "Surveys that directly ask employees how important pay is to them are likely to overestimate pay's true importance in actual decisions" (p. 158). If our interpretation (and that of Rynes et al.) of the research literature is accurate, then the correct true-false answer to the above statement is "false." In other words, people are more likely to underreport than to overreport th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
259
1
21

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(293 citation statements)
references
References 27 publications
12
259
1
21
Order By: Relevance
“…Perry, Mesch, and Paarlberg (2006) found that in public sector organizations, financial incentives for individuals is not that much effective; however, they stated that it depends on the organizational conditions. Every individual employee may not consider merit pay as a motivating factor (Rynes, Gerhart and Minette, 2004). Bates (2003) indicated that merit pay could be made as an attractive factor provided the merit pay rise should be not less than seven percent of the core pay so that it can be perceived as a motivating factor.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Perry, Mesch, and Paarlberg (2006) found that in public sector organizations, financial incentives for individuals is not that much effective; however, they stated that it depends on the organizational conditions. Every individual employee may not consider merit pay as a motivating factor (Rynes, Gerhart and Minette, 2004). Bates (2003) indicated that merit pay could be made as an attractive factor provided the merit pay rise should be not less than seven percent of the core pay so that it can be perceived as a motivating factor.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The availability of such rewards is an important source of work motivation (Rynes, Gerhart, & Minette, 2004), and researchers have found it has become an important element in employment relationships today (Tsui, Pearce, Porter, & Tripoli, 1997). An increase in availability of rewards for performance may elicit employees' reciprocation to their organizations, manifested in greater willingness to stay with the organization and contribution to its collective goal.…”
Section: Availability Of Rewards For Performancementioning
confidence: 99%
“…Pay is obviously a factor of great importance in the workplace (Rynes, Gerhart, & Minette, 2004), and it has been studied as a determinant and correlate of many different workplace variables. One of the major outcomes of pay is pay level satisfaction, which has also been the focus of much research.…”
mentioning
confidence: 99%